2014
DOI: 10.3329/jles.v7i0.20129
|View full text |Cite
|
Sign up to set email alerts
|

Flesh Estimation of Some SIS Fish

Abstract: Small Indigenous Species (SIS) of fishes of 18 species under ten families and five orders were selected for the experiment. The percentage and ratio of edible portions compared to their wastes (%) were determined. The percentage by weight after dressing and washing was found for Corica soborna as 97.76% and the lowest for Colisa fasciata as 57.40%, but the ratio of these weights were maximum on C. fasciata and minimum in C. soborna. Key words: SIS, fleshmvivsk: ch© ‡e ¶ ‡Yi Rb¨ cu vPwU eM© Ges `kwU †Mv ‡Îi AšÍ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 3 publications
0
4
1
Order By: Relevance
“…In our study, the observed maximum length of C. soborna was 5.0 cm TL irrespective of sex, which is higher than the reported value of (i) 2.70 cm (Sultana, 2012) from the Ganges River, Bangladesh (ii) 4.99 cm (Hossain et al, 2008) from the Mathabhanga River, Bangladesh (iii) 3.80 cm (Kamal, 1982) from the Ganga River, India, but lower than the maximum recorded length (TL= 5.3 cm) reported by Hossain et al (2017a) from the Ganges River, NW Bangladesh. Information on maximum length is crucial for the estimation of asymptotic length and growth coefficient of fishes, as required for planning and management of fisheries resources (Hossain et al, 2012a(Hossain et al, , 2017d(Hossain et al, , 2018Hossen et al, 2018;Khatun et al, 2019a).…”
Section: Discussioncontrasting
confidence: 92%
“…In our study, the observed maximum length of C. soborna was 5.0 cm TL irrespective of sex, which is higher than the reported value of (i) 2.70 cm (Sultana, 2012) from the Ganges River, Bangladesh (ii) 4.99 cm (Hossain et al, 2008) from the Mathabhanga River, Bangladesh (iii) 3.80 cm (Kamal, 1982) from the Ganga River, India, but lower than the maximum recorded length (TL= 5.3 cm) reported by Hossain et al (2017a) from the Ganges River, NW Bangladesh. Information on maximum length is crucial for the estimation of asymptotic length and growth coefficient of fishes, as required for planning and management of fisheries resources (Hossain et al, 2012a(Hossain et al, , 2017d(Hossain et al, , 2018Hossen et al, 2018;Khatun et al, 2019a).…”
Section: Discussioncontrasting
confidence: 92%
“…Small indigenous species (SIS) thrive well in freshwaters and can be grown easily in fallow water areas and marginal wetlands in the vicinity of agricultural lands, roads and houses where larger fish species cannot survive (Sultana, ). Therefore, the extensive culture of this species does not require much consideration and can be based on selected food items available in nature.…”
Section: Resultsmentioning
confidence: 99%
“…Both natural events and human-induced disasters have contributed to the degradation of aquatic ecosystems in Bangladesh, leading to the loss of conducive environments for SIS. As a consequence, SIS are facing severe threats, and are at a critical risk of extinction [ 11 ]. In earlier times, SIS were considered as weed fish and were removed from the culture ponds using chemicals and pesticides (rotenone, benzene hexachloride, saponins, calcium cyanamide, sodium cyanide, chlorine, calcium hypochlorite, sodium pentachlorophenate, and lime etc.).…”
Section: Introductionmentioning
confidence: 99%